Development of transparent eye shields for total skin electron beam radiotherapy. Issue 9 (11th July 2022) - Lucido, J. John; Veres, Andrew J.; Kehret, Shawn M.; Angeli, John A.; Highet, Robert D.; Foote, Robert L.; Lester, Scott C.; Deufel, Chris L.
Abstract: Purpose: For total skin electron (TSE) beam radiation therapy, the anterior eye and conjunctiva can be protected with eye shields to prevent keratitis, xerophthalmia, and cataractogenesis. Conventional metal eye shields can reduce patient balance by obscuring vision and thus increasing the risk for falls. We report on the design, fabrication, and clinical use of transparent acrylic eye shields for TSE. Methods: The primary design goals were a seven‐fold reduction in the dose to the anterior eye and conjunctiva to meet published dose‐recommendations, preservation of vision for the wearer, and biocompatibility for external use. Resembling thick swim goggles, the design features 23 mm thick acrylic lenses that are mounted in a 3‐D printed support structure that conforms to the eye socket and can be worn with a strap. Dose measurements were performed in a simulated Stanford‐technique treatment with an anthropomorphic phantom using Gafchromic EBT film Results: The transparent eye shields were manufactured using a 3D‐printer and CNC‐machine. Based on measurements from the simulated treatments for each of the eye shields, the eye shields provided a 12‐fold reduction in dose to the lens. After use in more than 200 fractions, the shields were well tolerated by patients, and there were no reports of any incidents or adverse events. Conclusion: Transparent TSE eye shields are able to reduce the dose to the eyes while maintaining vision during treatment at a reasonable cost.